Inhibition of NETs-mediated thromboinflammation alleviates hemorrhagic transformation after hyperglycemic stroke - Ziyuan Zhao; Yiming Ma; Wenjing Sun; Chengdi Liu; Longrui Wang; Yinru Jiang; Guanhua Du; Lianhua Fang; Linglei Kong (Journal of Translational Medicine, 2026)
Abstract Background Hemorrhagic transformation (HT) is a serious complication of acute ischemic stroke. Hyperglycemia, an independent risk factor, exacerbates stroke by inducing HT and increases mortality and disability, which is a major unmet clinical need. Neutrophil extracellular traps (NETs), recognized for exacerbating inflammatory and thrombotic diseases, are emerging as potential therapeutic target in stroke. However, the targets and mechanisms of hyperglycemia-induced HT and the roles of NETs in HT are unclear, leading to a lack of effective therapeutic strategies and limiting clinical treatment. Methods This study aimed to investigate the correlation between NETs and hyperglycemia-induced HT, and to explore the effects and underlying mechanisms of NETs in hyperglycemia-induced HT. Firstly, GEO analysis was used to predict the regulatory mechanisms of hyperglycemia-induced HT. Stroke patients’ blood samples and rat neutrophils were collected to investigate the correlation between NETs and glucose level. A hyperglycemia-induced HT rat model was established to investigate the correlation between NETs level and HT severity. Both NETs inhibitor Cl-amidine (20 mg·kg −1 , i.p.) and degrader DNase I (10 mg·kg −1 , i.v.) were utilized to demonstrate the effects of NETs in hyperglycemia-induced HT. Lastly, RNA-seq, immunofluorescence, and ELISA analyses were performed to investigate the mechanisms by which NETs contribute to hyperglycemia-induced HT. Results GEO analysis results firstly suggested that hyperglycemic stroke-induced HT may be related to the regulation of NETs, which was confirmed in stroke patients that NETs levels were positively correlated with blood glucose. Further in vivo experiment suggested that both NETs and cerebral hemoglobin content peaked at 1d after stroke, and a linear relationship was observed between HT severity and NETs levels in hyperglycemic MCAO rats. NETs inhibition with Cl-amidine and DNase I could improve hyperglycemia-induced HT in rats. Inhibition of NETs alleviated thromboinflammation by decreasing the levels of inflammatory factors such as TNF-α and IL-8, and thrombosis-related factors such as vWF, TAT and fibrinogen in hyperglycemia-induced HT rats. Conclusions This study provides the first evidence that NETs exacerbate hyperglycemia-induced HT through thromboinflammation. NETs may be a potential biomarker and novel target for HT prediction and treatment after stroke.